FINDYOURHELP: UM MÓDULO PARA APOIAR A BUSCA POR ESPECIALISTAS NO AMBIENTE VIRTUAL DE APRENDIZAGEM MOODLE - Santos, Marcos Lapa dos (2010)
This study examines the adoption of text mining techniques with the concepts of knowledge management to support the search for experts in the discussion forums on Moodle environment. The solution, called FindYourHelp, was developed as an additional Moodle plugin and allows the execution of a text categorization algorithm at the time of a message posting. In order to validate the tool applicability, a feasibility study was developed where the main intent was to execute the solution in order to analyze the messages of three separate disciplines from two institutions of higher education in Bahia. The study results showed that the proposed solution was successful in most analyzed cases. The three disciplines professors, participated in the results evaluation indicated by FindYourHelp and confirmed its reliability in the process of automatically identifying experts in academic discussion forums